Il re si diverte e muore: un itinerario dal grottesco all’assurdo (Itinera, 2013)
This essay first discusses Victor Hugo’s defence of grotesque, his defence of Shakespeare, his achievements in Le roi s’amuse, and also the limitations due to his prophetic style. Piave and Verdi go further in Il Rigoletto, especially in the dramatic polyphony of opposite voices and points of view. Finally, we follow the creation of new kings, from Jarry’s Ubu to Ionesco’s Le roi se meurt: the absurd dimension which the romanticists had felt but had refused to surrender to is in the absurd and in most post-dramatic theatre a double impossibility of giving sense to the world and language to tragedy.